2021
DOI: 10.1002/joom.1159
|View full text |Cite
|
Sign up to set email alerts
|

Should firms use digital work instructions?—Individual learning in an agile manufacturing setting

Abstract: New technological innovations in robotics, automation, and digitization enable agile manufacturing, smaller lot sizes, and quicker changes to the product and the production process. In such environments, learning is important, since workers must learn new tasks and adapt to frequent changes quickly. In an experimental study, we compare digital work instructions with traditional paper-based ones, the latter still being common in today's quality management systems. Our analysis is based on subjects working in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…Furthermore, if the production process falls within the zone of use of modern visualization tools, it is necessary to decide which type of visualization tools will be selected and how they will be used. The inappropriateness of a combination of paper and digital manuals has already been demonstrated [9]. The characteristics of manufacturing processes that influence the selection of a modern visualization tool belong to groups A and C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if the production process falls within the zone of use of modern visualization tools, it is necessary to decide which type of visualization tools will be selected and how they will be used. The inappropriateness of a combination of paper and digital manuals has already been demonstrated [9]. The characteristics of manufacturing processes that influence the selection of a modern visualization tool belong to groups A and C.…”
Section: Discussionmentioning
confidence: 99%
“…The current trend is to move away from paper manuals [8]. Digitized manuals lead to better overall results and a reduction in errors [9]. Some workers may need additional support that a conventional digital manual may not provide [10].…”
Section: Introductionmentioning
confidence: 99%
“…In response to technological advancements and the trajectory of automation, it is imperative to thoroughly comprehend and adjust to these transformations to guarantee the labor market's adaptability and sustainability. This approach is vital for fostering a more inclusive and dynamic work environment for the future, with the aim of realizing sustainable, inclusive, and prosperous development [16]. Therefore, sustainable employment has become a key task.…”
Section: Sustainable Employmentmentioning
confidence: 99%
“…Currently, academic research on the impact of digitization on employment is mainly focused on the macro level, primarily from the perspectives of industrial structure upgrading and technological progress, with limited research on the micro level [15][16][17]. Meanwhile, there is still controversy over the relationship between digitization and employment, and there is a research gap regarding digitization and sustainable employment.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Avgerinos et al (2020) examined how surgery operation failure events promoted learning and affected task execution over time in a European hospital. Recently, Letmathe and Rößler (2022) compared worker learning via emerging digital work instructions versus traditional, paper‐based work instructions. They found that animated, interactive, digital work instructions show promise to stimulate learning in agile manufacturing environments.…”
Section: Looking Back – Tm Research Published In Jommentioning
confidence: 99%